Food safety management - Davlyatova Mavlyuda Baxtiyorovna (Zien Journals, 2022)
The lack of single international requirements for the system of Product Safety and Quality Management in food enterprises ISO 22000 series "Food Safety Management System. The need to develop"requirements for all of the supply chain" came out, and it was introduced from September 2005.
Keywords: HACCP; market relations; ISO 9001:2000; GMP